Estudo sobre o tratamento térmico de envelhecimento interrompido T6I4-65 e influência na propagação de trinca por fadiga em uma liga de alumínio AA7050 - Lima, Luis Otavio Ribas de (2014)
Aluminum alloys have been the primary material of choice for the aircraft due to their properties such as low density, high mechanical and corrosion resistance. Commercial aircraft apply aluminum alloys for the fuselage, wings and supporting structure due to the extensive knowledge in design and production of aluminum components, and most importantly, aluminum alloys continue to be developed, keeping it highly competitive. A great development happen with the heat-treatable alloys, which allow improvement of the mechanical properties. Among this alloys stand out the Al-Zn-Mg-Cu series, known for high strength, toughness and corrosion resistance. The improvement of those alloys occurs by the precipitation of nanometric particles MgZn2, called η phase. This study’s aim was to promote an interrupted heat treatment T6I4-65 in an AA7050 aluminum alloy, with fatigue crack growth resistance as priority. Interrupted heat treatments’ goal is optimizing the consumption of solute atoms during process of nucleation and growth of precipitates as a finely dispersion. The T6I4-65 condition obtained was analyzed by differential scanning calorimetry, DSC, optical and electronic microscopy, mechanical tests as hardness, tensile and fatigue crack growth. The T6I4-65 treatment results in a microstructure with a fine dispersion of precipitated phase η’, about 75% smaller than those resulting from in current use, T7451. This microstructure resulted in a reduction of up to 24% in fatigue crack growth rate compared to that resulting from T7451 treatment, keeping the ductility of 17% of area reduction and yield strength higher than 400MPa.